Air pollution, food production and food security: A review from the perspective of food system - Feifei Sun; Yun DAI; Xiaohua Yu (Journal of Integrative Agriculture, 2017)
Air pollution negatively impacts food security. This paper reviews the current literature on the relationship between air pollution and food security from the perspective of food system. It highlights that agricultural emissions which substantially contribute to air pollution could happen at every stage along the food supply chain. Meanwhile, air pollution can not only affect plant growth and animal health but also shift market equilibrium of both agro-inputs and outputs in the food supply chain and thereby affect food security indirectly. Furthermore, this study evaluates the effects of agricultural policy and energy policy on food security and air pollution, respectively, and provides an overview of potential policy instruments to reduce air pollution while ensuring food security. Finally, we identify the remaining research and policy issues for further studies, mainly focusing on the study of household's bounded rational behaviors and the issue of rural aging population.